Analisis Kesulitan Belajar Siswa Kelas VIII D MTsN 5 Jember - Dadang Abdillah (Program Studi Pendidikan IPA FKIP Universitas Jember, 2019)
Learning difficulties are a disorder of students in learning from speaking, writing, listening, reading, and other abilities. The purpose of this study was to determine the type of learning difficulties and factors that influence student learning difficulties in class VIII D MTsN 5 Jember. This research formulates the problem of what types of difficulties are experienced and the factors that influence student learning difficulties in class VIII D MTsN 5 Jember. The population of this study were all class student in class VIII D MTsN 5 Jember. Data collection techniques using interview method. The results of the study show that there are some chikdren whi still experience difficulties in learning. In this case it is influenced by two factors, namely internal factors and external factors, internal factors that cause children to experience learning difficulties are the lack of interest from the student to learn, while external factors that affect student difficulties in learning can be grouped into three, namely family, school and community environment. From the results of this study it can be concluded that many learning difficulties are experienced by students in class VIII D MTsN 5 Jember caused by several factors that can be classified into two factors, namely internal factors (from within students) and external factors (from outside the student).